Clinical Outcomes in Critically Ill Coronavirus Disease 2019 Patients: A Unique New York City Public Hospital Experience - Mukherjee, Vikramjit (Crit Care Explor, 2020)
To explore demographics, comorbidities, transfers, and mortality in critically ill patients with confirmed severe acute respiratory syndrome coronavirus 2. DESIGN: Retrospective cohort study. SETTING: Data were collected from a large tertiary care public hospital ICU that is part of the largest public healthcare network in the United States. PATIENTS: One-hundred thirty-seven adult (≥ 18 yr old) ICU patients admitted between March 10, 2020, and April 7, 2020, with follow-up collected through May 18, 2020. INTERVENTIONS: None. MEASUREMENTS: Demographic, clinical, laboratory, treatment, and outcome data extracted from electronic medical records. MAIN RESULTS: The majority of patients were male (99/137; 72.3%) and older than 50 years old (108/137; 78.9%). The most reported ethnicity and race were Hispanic (61/137; 44.5%) and Black (23/137; 16.7%). One-hundred six of 137 patients had at least one comorbidity (77.4%). One-hundred twenty-one of 137 (78.1%) required mechanical ventilation of whom 30 (24.8%) moved to tracheostomy and 46 of 137 (33.6%) required new onset renal replacement therapy. Eighty-two of 137 patients (59.9%) died after a median of 8 days (interquartile range 5–15 d) in the ICU. Male sex had a trend toward a higher hazard of death (hazard ratio, 2.1 [1.1–4.0]) in the multivariable Cox model. CONCLUSIONS: We report a mortality rate of 59.9% in a predominantly Hispanic and Black patient population. A significant association between comorbidities and mortality was not found in multivariable regression, and further research is needed to study factors that impact mortality in critical coronavirus disease 2019 patients. We also describe how a public hospital developed innovative approaches to safely manage a large volume of interhospital transfers and admitted patients.